2005
DOI: 10.1016/j.jcis.2004.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The electrokinetic properties of latex particles: comparison of electrophoresis and dielectrophoresis

Abstract: A comprehensive study of the AC and DC electrokinetic properties of submicrometre latex particles as a function of particle size and suspending medium conductivity and viscosity is presented. Electrophoretic mobility and dielectrophoretic cross-over results were measured for particle diameters ranging from 44 to 2000 nm. The zeta potentials of the particles were calculated from the electrophoretic mobility data for different suspending medium conductivities, using various models, with and without the inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
263
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(276 citation statements)
references
References 40 publications
12
263
1
Order By: Relevance
“…Counterions are more mobile in the diffuse layer than in the Stern layer, and contribute separately to the overall magnitude of K s and thus to the DEP behavior of nanoparticles. [28][29][30][31] A comprehensive study of the ac and dc electrokinetic properties of latex nanoparticles, as a function of suspending medium conductivity and viscosity, has been reported by Ermolina and Morgan, 32 and a theoretical modeling of the DEP force that takes into account the influence of the electrical double layer has been presented by Zhou et al 33 Analysis of the normal and tangential ionic currents that occur around and at the surface of a particle, when its diameter approaches and becomes smaller than the width of its own electrical double layer, indicates that a capacitance effect contributes to the total polarizability of the particle, and exceeds the influence of the surface conductance K s . 34,35 Basuray and Chang 34 also showed that the DEP cross-over frequency for nanocolloids is inversely proportional to the RC time constant of the diffuse layer component of the electrical double layer.…”
Section: ͑15͒mentioning
confidence: 99%
“…Counterions are more mobile in the diffuse layer than in the Stern layer, and contribute separately to the overall magnitude of K s and thus to the DEP behavior of nanoparticles. [28][29][30][31] A comprehensive study of the ac and dc electrokinetic properties of latex nanoparticles, as a function of suspending medium conductivity and viscosity, has been reported by Ermolina and Morgan, 32 and a theoretical modeling of the DEP force that takes into account the influence of the electrical double layer has been presented by Zhou et al 33 Analysis of the normal and tangential ionic currents that occur around and at the surface of a particle, when its diameter approaches and becomes smaller than the width of its own electrical double layer, indicates that a capacitance effect contributes to the total polarizability of the particle, and exceeds the influence of the surface conductance K s . 34,35 Basuray and Chang 34 also showed that the DEP cross-over frequency for nanocolloids is inversely proportional to the RC time constant of the diffuse layer component of the electrical double layer.…”
Section: ͑15͒mentioning
confidence: 99%
“…a lower protein conductivity and consequently negative Clausius-Mosotti factor. The influence of dynamic polarization phenomena on nanocolloid polarization was recently reported 42,44 and may also hold for proteins. In addition to the ionic transport in the double-layer, the electrophoretic motion of proteins may also be responsible for the here observed transition to negative DEP.…”
Section: E Influence On Protein Dep Due To Surfactantsmentioning
confidence: 88%
“…25 For nanocolloids, corrections to the classical Maxwell Wagner O'Konski approach were suggested due to the apparent size dependent crossover frequencies. 41,42 These refinements take into account charge movement in the Stern layer and the diffuse layer. 43,44 A standard model employing Poisson-Nernst-Planck equations was also suggested accounting for ionic migration, convection, diffusion, and electrophoretic migration.…”
Section: Introductionmentioning
confidence: 99%
“…1 Functionalized latex particles are frequently used as an experimental model of charged particles. [2][3][4][5][6][7][8] These particles have acid-base ionizable groups, which are responsible for the surface charge due to their dissociation and subsequent release of counterions in solution. The properties of this kind of materials are strongly influenced by the electrostatic effects that take place at the interface.…”
Section: Introductionmentioning
confidence: 99%